Athlete fact sheet RED-S (Sport Scotland Institute of Sport, 2022)
RED-S stands for Relative Energy Deficiency In Sport. It is described as "Impaired physiological function including, but not limited to, metabolic rate, menstrual function, bone health, immunity, protein synthesis, cardiovascular health caused by relative energy deficiency" It is when the energy we take in through fuel doesn`t match the energy we expend through activity, and therefore the energy our bodies have available to maintain organs/cells, our temperature, our immune function, growth and reproduction. The factsheet informs about:' What is RED-S? How can RED-S affect performance? How can RED-S b e avoided?